Participatory Synergy of School Committees in Merdeka Curriculum Implementation: A Multisite Study in ECE - Lailatul Tarwikhi; Ahmad Thohirin; M Furqon Wahyudin (DINAMIKA : Jurnal Kajian Pendidikan dan Keislaman, 2026)
This study aims to analyze the management of partnerships between schools and parent associations (school committees) in enhancing the effectiveness of the Merdeka Curriculum implementation at the Early Childhood Education (ECE) level. The focus of the study encompasses the processes of planning, organizing, implementing, and evaluating partnerships, as well as their contribution to improving the quality of educational services. This research employed a qualitative approach with a multisite study design conducted at TK Muslimat 16 Tanwirul Hijaa and TK PGRI 4 in Bangil District, Pasuruan Regency. Data were collected through limited participatory observation, in-depth semi-structured interviews with principals, teachers, and parent association administrators, and document analysis. Data analysis was carried out interactively through the stages of data condensation, data display, and conclusion drawing, while data trustworthiness was ensured through source and technique triangulation, member checking, and prolonged field involvement. The research findings indicate that school–parent partnership management that is planned participatively and implemented systematically is able to increase active parental involvement, strengthen support for learning based on the Merdeka Curriculum, and enhance satisfaction with ECE services. Effective partnerships are reflected in intensive two-way communication, parental involvement as guest teachers and home project mentors, and the collaborative execution of program evaluations. These findings confirm that horizontal and transformational partnership governance constitutes a key strategy to optimize children's growth and development achievements and to sustain the quality of early childhood education services.